Ethics Of Government Organizations In Indonesia - Dini Vientiany; Fiarinda Putri Syahrani; Mutiara Liza; Rini Fadilla Tunnisa (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Ethical values that live and apply in a society, are not just personal beliefs for its members, but also become a set of institutionalized norms. In other words, an ethical value must be a reference and guideline for action that brings moral consequences and influences. In government ethics, there is a prevailing assumption that through ethical appreciation, an apparatus will be able to build a commitment to make himself an example of goodness and maintain government morality.